Plurilingual Classroom Practices and Participation Analysing Interaction in Local and Translocal Settings - Masats, Dolors; Nussbaum, Luci (Taylor & Francis, 2022)
Plurilingual Classroom Practices and Participation contributes to a better understanding of plurilingual education in Catalonia by providing a description of the interactional resources mobilised by learners as social actors. This volume is a collection of studies that show interactions containing plurilingual and multimodal sequences that illustrate moments of potential acquisition of aspects of language use. Analysing data collected through ethnographic fieldwork, the studies explore interactions in primary, secondary, and tertiary milieus as well as non-formal settings and examine how participants organise their interaction, their ways of participating, and the resources they mobilise for them. The linguistic policies of the educational settings studied establish the use of a given language but contain samples of plurilingual practices in which languages like Arabic, Catalan, English, French, Greek, Mandarin, Punjabi, Riffian Berber, Spanish and Urdu come into play. The chapters explore the links between these practices and the construction of participation in the ongoing interaction. Although focused on language education in Catalonia, results can be transferred to classrooms worldwide which host plurilingual learners. Thus, the volume is an excellent resource for teachers and researchers interested in plurilingual education and can be used as a reference book in doctoral studies and teacher training programmes in this research field.